IMPLEMENTATION OF CREDIT GRANTING BY A CUSTOMARY VILLAGE CREDIT INSTITUTION TO OTHER KRAMA WITHOUT AN AGREEMENT OF COOPERATION BETWEEN CUSTOMARY VILLAGES - I Made Dedy Priyanto; I Wayan Novy Purwanto (International Journal of Innovative Technologies in Social Science, 2022)
This study aims to determine the cooperation agreement between Customary Villages as the basis for Village Credit Institution (LPD) in providing Denpasar credit to other village krama and to find out the implementation of credit granting by LPD in the Denpasar area to other village krama without any cooperation agreement between Customary Villages. The research method used is a type of empirical legal research. The results of this study are that inter-village cooperation agreements are regulated in the Bali Province Regional Regulation Number 3 of 2017 concerning LPDs emphasized in Article 7 paragraph (1) letter c where it is stated that LPDs can provide credit to other village krama on condition that there is cooperation between villages and collaboration between villages in the form of an inter-village cooperation agreement that was decided by the cooperating village, but in granting credit to other village krama, the intervillage cooperation agreement was not implemented which resulted in the credit agreement made between the LPD and other village krama considered invalid because it violated regional regulations and The Governor’s Regulation on LPD and the agreement is null and void because it violates the objective conditions of an agreement. While the granting of credit to other village krama carried out by the LPD is not much different from the local village krama, the fundamental difference is the conditions when other village krama want to apply for credit to the LPD, each LPD provides different conditions to other village krama who wish to apply credit. Based on the results of research and interviews, there are several factors that the LPD provides credit to other village krama without an agreement due to profit factors, ignorance of the law, no sanctions given, family factors and village potential factors.